Review of Development of Live Vaccines against Leishmaniasis - Feiz Haddad, Mohammad Hossein; Lomei, Jalal; Shokri, Azar; Habibpour, Habib; Rezvan, Hossein; Nourian, Alireza; Mahmoudi, Mohammad Reza (Journal of Child Science, 2021)
Leishmaniasis is a serious public health problem in both tropical and temperate regions, caused by protozoan parasites of the genus Leishmania. Cutaneous leishmaniasis is the most common form of leishmaniasis worldwide. After recovery from the initial infection in most of the patients, a long-lasting natural immunity will be established. In individuals with HIV infection or in immune deficient patients, the more dangerous forms can occur. Despite many attempts, there is no efficient vaccine for leishmaniasis. The main concern for live-attenuated vaccines is the possibility of returning to the virulent form. Therefore, the safety is an important point in designing a successful vaccine. Nonvirulent parasites as vaccine candidates are achievable through gamma-irradiation, long-term culture, random mutations induced by chemical agents, and temperature-sensitive mutations. The type of change(s) in such parasites is not known well and drawbacks such as reversion to virulent forms was soon realized. Leishmania tarentolae with capacity of adaptation to mammalian system has a potential to be used as nonpathogenic vector in vaccine programs. Due to its nonpathogenic intrinsic property, it does not have the ability to replace with the pathogen form. Moreover, the main problems are associated with the production of live vaccines, including lyophilization, storage, standards, and quality control that must be considered. In this review, we focused on the importance of different approaches concerning the development of a live vaccine against leishmaniasis.
Keywords: Leishmania; leishmaniasis; live-attenuated; vaccine